Reforming Labor and Product Markets : Some Lessons from Two Decades of Experiments in Europe - Boeri, Tito (IMF Working Papers; Working Paper ;, 2005)
This paper evaluates European structural reforms over the last 20 years, in light of economic theory predictions about interactions between labor and product market reforms. Reforms in labor markets occur at higher frequencies than in product market, which are, however, more coherent. These asymmetries can be explained by the nature of political obstacles to reforms in the two domains. Labor market reforms can exploit institutional trade-offs; notably, reforms can trade labor market flexibility with state-provided unemployment insurance and can be applied only to new entrants in the market without affecting the set of regulations applied to existing workers. These two-tier strategies are infeasible in product markets, since incumbent firms can easily drive away new entrants. In product markets, however, it is possible to shift responsibilities to supranational authorities, resisting pressures of national lobbies.